Dynamic Cumulative Residual and Past Inaccuracy Measures - Vikas Kumar; H.C. Taneja (Journal of Statistical Theory and Applications (JSTA), 2015)
In this paper, we have developed measures of dynamic cumulative residual and past inaccuracy. We have studied characterization results under proportional hazard model in case of dynamic cumulative residual inaccuracy and under proportional reversed hazard model in case of dynamic cumulative past inaccuracy measure. We have characterized certain specific lifetime distributions using the measures proposed. Some generalized results have also been considered.